2021
DOI: 10.3390/agriculture11040356
|View full text |Cite
|
Sign up to set email alerts
|

Alley Cropping Mitigates the Impacts of Climate Change on a Wheat Crop in a Mediterranean Environment: A Biophysical Model-Based Assessment

Abstract: Introduction: Climate change (CC) and the increased occurrence of extreme climatic events pose a serious threat to crop yields and their stability worldwide. This study analyzed the CC mitigation potential of an alley cropping system on crop physiological stresses and growth as compared to a monoculture system. Materials and Methods: Growth of winter durum wheat, cultivated alone (agriculture) and in combination with hybrid walnut (agroforestry), was simulated with the Hi-sAFe agroforestry model, as driven by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The temporal differences in the developmental stages of crop and tree are important. For example, the impact on crop yield is small, if crops have reached important developmental stages before trees are fully foliated; this is the case for late leafing trees such as walnut (Reyes et al., 2021). Past research found indications for morphological and/or physiological adaptation strategies of field crops to shade conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal differences in the developmental stages of crop and tree are important. For example, the impact on crop yield is small, if crops have reached important developmental stages before trees are fully foliated; this is the case for late leafing trees such as walnut (Reyes et al., 2021). Past research found indications for morphological and/or physiological adaptation strategies of field crops to shade conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The Rib watershed, northwestern highland, Ethiopia, will continue to experience climate change with mean annual temperature increasing by 0.24°C per decade and an increase in annual and Kiremt rainfall and a decrease in Belg rainfall [20]. Moreover, simulations of future climate change impacts with the Hi-sAFe agroforestry model indicates that heat, drought, and nitrogen stresses increased about twofold from Past to the future (2031-2070) in the case of Mediterranean Environment [21].…”
Section: Climate Change and Its Impact On Sustainable Agricultural Cr...mentioning
confidence: 99%
“…Agroforestry systems could reduce maize yield losses where climate change threatens maize productivity in Ethiopia [51]. For instance, [21] indicate 20-35% reduced climate change impacts like heat, drought, and nitrogen stresses in an agroforestry systems with mediumsized trees otherwise which would be increased about twofold from past to future. Parkland agroforestry has mutual benefits on providing food security to small-scale farmers and improving the climate change adaptation and mitigation strategies in the case of Tigray Region, Ethiopia [52].…”
Section: Parkland Agroforestry System and Practicementioning
confidence: 99%
“…This increases the water and nutrient use efficiency of the system [50], but leaves even less water for deep percolation and groundwater recharge. Reducing the radiation input through shading improves the growth condition for the annuals in most circumstances, so that reduced radiation input is compensated for by less stress through high temperatures and slower development [51,52], despite higher night temperatures [53]. A better growing crop, however, consumes more water and nutrients.…”
Section: Water Regulationmentioning
confidence: 99%
“…The Hi-sAFe model is potentially able to address all the above-mentioned feedback loops, and has done so with many of them already [51]. What is still missing is the feedback between soil moisture and soil organic matter mineralization/plant N uptake, and the question of whether agroforestry would really reduce N leaching or would just make zoning of N fertilizer demand even more complicated, with undesired effects on N leaching.…”
Section: Water Regulationmentioning
confidence: 99%